Increasing Purchase Intention through Storytelling Marketing and Experiential Marketing with Brand Equity as an Intervening Variable - Kadek Danthiswari Gelgel; I Gusti Ayu Wimba; Ida Ayu Putu Widani Sugianingrat (Management and Applied Social Studies Review, 2024)
Purpose – Rangrang weaving is a traditional craft product inherited from the ancestors of Nusa Penida, Bali. IKM Ngurah Gallery as a rangrang weaving company, understands the importance of implementing marketing strategies. Proper storytelling and experiential marketing will have a positive impact on increasing consumer purchasing intentions. Methodology – This research used descriptive quantitative methods, the sample size was 114 respondents, data collection techniques used questionnaires, and data were analyzed using SEM-PLS. Findings – The result of the research show that storytelling marketing influences purchase intention and experiential marketing influences purchase intention. Storytelling marketing influences brand equity and experiential marketing influences brand equity. Brand equity influences purchase intention. The brand equity variable has a mediating role between the storytelling marketing variable and purchase intention. The brand equity variable has a mediating role between the experiential marketing variable and purchase intention.